Pengembangan perangkat pembelajaran sekolah dasar berbasis Understanding by Design - Desi Eka Pratiwi; Leni Yuliana (Curricula: Journal of Curriculum Development, 2026)
Learning in elementary schools still faces challenges in aligning learning objectives, assessment, and instructional activities, which limits students’ conceptual understanding. This study aims to develop Understanding by Design (UbD)-based learning tools for elementary schools that meet the criteria of validity, practicality, and effectiveness. The research employed a research and development (RnD) approach using the ADDIE model. The developed learning tools comprise teaching modules, instructional materials, and authentic assessment instruments grounded in the backward design principle. Data were collected through expert validation, observation of learning implementation, teacher and student response questionnaires, and learning outcome tests, and were analyzed using descriptive, quantitative, and qualitative methods. The results showed that the UbD-based learning tools achieved very high validity. Practicality was indicated by implementation rate and positive responses from teachers and students. The learning tools were also effective, as shown by improved student learning outcomes, with classical mastery. Therefore, UbD-based learning tools are feasible and effective for improving elementary school learning oriented toward conceptual understanding.